Development of Contextual-Based Narrative Text Module for Students of 7th Grade Junior High School - Shinta Larasati; Edi Suyanto; Siti Samhati (Budapest International Research and Critics University, 2022)
The problem in this study is related to the limitations of teaching materials in narrative text materials in schools. This study aims to produce, develop, and describe the feasibility of teaching material products in the form of